Heart rate variability in patients with post-traumatic stress disorder or borderline personality disorder: relationship to early life maltreatment - Meyer, Peter-Wolfgang; Müller, Laura Elisa; Schmidinger, Ilinca; Bohus, Martin; Herpertz, Sabine; Bertsch, Katja (Journal of neural transmission, 2016)
Traumatic experiences have severe impact on the autonomous nervous system. Heart rate variability (HRV) is a reliable psychophysiological marker for the autonomous nervous system functioning. Reduced vagally mediated HRV has been found in patients with post-traumatic stress disorder (PTSD) and, in some studies, in patients with borderline personality disorder (BPD). In this study, we compared HRV parameters of patients with PTSD, current BPD, and BPD in remission with healthy volunteers in a 5 min resting-state electrocardiogram recording. 91 unmedicated female participants took part in the study (18 with PTSD, 27 with the current BPD, 23 with BPD in remission, and 23 healthy volunteers). We found significant group differences in both time-domain and frequency-domain (total power, low-frequency and high-frequency power) HRV parameters. Root mean square of the successive differences (RMSSD) was lowest in patients with PTSD (M = 48.6 ms, SD = 23.5 ms) followed by patients with BPD in remission (M = 57.7 ms, SD = 31.5 ms) and patients with the current BPD (M = 71.1 ms, SD = 44.5 ms), while the highest RMSSD was found in healthy volunteers (M = 84.1 ms, SD = 41.7 ms). Variance of HRV was higher in patients with BPD than in patients with PTSD. In addition, RMSSD was significantly negatively correlated with self-reported early life maltreatment assessed with the Childhood Trauma Questionnaire. Our findings point out a complex interaction between traumatic experiences, the functioning of the autonomic nervous system, and psychopathology. Alterations in HRV might be related to early life maltreatment or associated psychological factors rather than diagnostic entities.